2016
DOI: 10.4103/2249-4863.201176
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and self-care practices regarding diabetes among patients with Type 2 diabetes in Rural Sullia, Karnataka: A community-based, cross-sectional study

Abstract: Introduction:Diabetes is a lifestyle disease which requires a multipronged approach for its management, wherein patient has an important role to play in terms of self-care practices, which can be taught to them by educational programs. To develop such an educational program, a baseline assessment of knowledge and self-care practices of patients, needs to be made. The two objectives of the study were to estimate the knowledge of diabetic patients regarding the disease and its complications, and to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 12 publications
10
43
4
2
Order By: Relevance
“…Similar findings revealed in other studies in India using similar tool for assessment. [3][4][5] In our study duration of diabetes was significantly related to better self-care practices, similarly Rajasekharan et al in Mangalore found better practices among participants with more duration of diabetes in few aspects, which might be due to accrued experience and exposure to self-care education measures also. 6 Likewise disease duration had significant association with practices in study by Tol et al 7 In present study self-care was significantly associated with age and education, and as predictable, were better among graduates and patients above 60 years of age.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similar findings revealed in other studies in India using similar tool for assessment. [3][4][5] In our study duration of diabetes was significantly related to better self-care practices, similarly Rajasekharan et al in Mangalore found better practices among participants with more duration of diabetes in few aspects, which might be due to accrued experience and exposure to self-care education measures also. 6 Likewise disease duration had significant association with practices in study by Tol et al 7 In present study self-care was significantly associated with age and education, and as predictable, were better among graduates and patients above 60 years of age.…”
Section: Discussionsupporting
confidence: 70%
“…15 Consumption of fruits and vegetables was less common practice and followed by 47.6% in present study while it was only 3% in Sullia. 3 At least 30 minutes of moderate intensity activity on most days is effective in achieving good glycaemic control by reducing insulin resistance. Heterogeneous results had been observed in different studies in India, however in this study 52.3% patients followed at least 30 minutes of continuous physical activity on most days of past week.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are comparable to the findings of Dinesh et al who found that majority (60%) of the study participants checked their blood sugar levels regularly and performed some form of physical exercise. 12 Similar findings were reported by and Gopichandran et al who reported that majority of participants followed correct practices for management and monitoring of blood sugar levels. 13…”
Section: Practices Towards Diabetes Mellitus Its Complications and Msupporting
confidence: 86%
“…This indicates that some patients are still under the misconception that diabetes is completely curable. 20 In a study done in Chennai (CURES-9), only 11.9% of the subjects reported that obesity is a risk factor for diabetes but in our study 73.7% were aware of the association of diabetes and obesity. This indicates that diabetics have become more conscious of their weight and have realized that weight gain could lead to complications of diabetes.…”
Section: -13mentioning
confidence: 68%